101k views
4 votes
(-4 × 5.2) − (-3 × -4/5)=
) =

User Om Sao
by
5.3k points

1 Answer

3 votes

Answer:


=-23.2

Explanation:


\left(-4* \:5.2\right)-\left(-3\left(-(4)/(5)\right)\right)\\\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a,\:-\left(-a\right)=a\\=-4* \:5.2-3* (4)/(5)\\4* \:5.2=20.8\\4* \:5.2\\\mathrm{Multiply\:the\:numbers:}\:4* \:5.2=20.\\=20.8\\3* (4)/(5)=(12)/(5)\\3* (4)/(5)\\\mathrm{Multiply\:fractions}:\quad \:a* (b)/(c)=(a\:* \:b)/(c)\\=(4* \:3)/(5)\\\mathrm{Multiply\:the\:numbers:}\:4* \:3=12\\


=(12)/(5)\\=-20.8-(12)/(5)\\\mathrm{Convert\:element\:to\:a\:decimal\:form}\\(12)/(5)=2.4\\=-20.8-2.4\\\mathrm{Subtract\:the\:numbers:}\:-20.8-2.4=-23.2\\=-23.2

User Yves Blusseau
by
5.1k points